Pulmonary Laser Metastasectomy by 1318-nm Neodymium-Doped Yttrium-Aluminum Garnet Laser: A Retrospective Study About Laser Metastasectomy of the Lung. (April 2018) - Porrello, Calogero; Gullo, Roberto; Vaglica, Antonino; Scerrino, Gregorio; Salamone, Giuseppe; Licari, Leo; Raspanti, Cristina; Gulotta, Eliana; Gulotta, Gaspare; Cocorullo, Gianfranco
Background . The lungs are among the first organ affected by remote metastases from many primary tumors. The surgical resection of isolated pulmonary metastases represents an important and effective element of therapy. This is a retrospective study about our entire experience with pulmonary resection for metastatic cancer using 1318-nm neodymium-doped yttrium-aluminum garnet laser. Method . In this single-institution study, we retrospectively analyzed a group of 209 patients previously treated for primary malignant solid tumors. We excluded 103 patients. The number and location of lesions in the lungs was determined using chest computed tomography and positron emission tomography-computed tomography. Disseminated malignancy was excluded. All pulmonary laser resections are performed via an anteroaxillary muscle-sparing thoracotomy. All lesions were routinely removed by laser with a small (5-10 mm) margin of the healthy lung. Patients received systematic lymph node sampling with intraoperative smear cytology of sampled lymph nodes. Results . Mortality at 2 years from the first surgery is around 20% (10% annually). This value increases to 45% in the third year. The estimated median survival for patients who underwent the first surgery is reported to be approximately 42 months. Conclusion . Our results show that laser resection of lung metastases can achieve good result, in terms of radical resection and survival, as conventional surgical metastasectomy. The great advantage is the possibility of limiting the damage to the lung. Stapler resection of a high number of metastases would mutilate the lung.